Lung ICAM‐1 and ICAM‐2 support spontaneous intravascular effector lymphocyte entrapment but are not required for neutrophil entrapment or emigration inside endotoxin‐inflamed lungs. Issue 5 (28th January 2016) - Petrovich, Ekaterina; Feigelson, Sara W.; Stoler‐Barak, Liat; Hatzav, Miki; Solomon, Adam; Bar‐Shai, Amir; Ilan, Neta; Li, Jin‐Ping; Engelhardt, Britta; Vlodavsky, Israel; Alon, Ronen
Abstract : The pulmonary vasculature constitutively expresses the integrin lymphocyte function‐associated antigen‐1 ligands intercellular adhesion molecule (ICAM)‐1 and ‐2. In this study, effector T cells were temporarily entrapped by the lung vasculature on their way to inflamed lymph nodes, and this entrapment was strongly reduced in ICAM‐1 and ‐2 double‐deficient mice (79 and 86% reduction for CD8 + and CD4 + effectors, respectively, compared with wild‐type mice). Although the pulmonary vasculature has been suggested to be masked by the heparan sulfate‐containing glycocalyx, which is susceptible to heparanase‐mediated shedding, lung and lymphocyte heparanase have been found to be unnecessary for this entrapment. Systemic LPS induced rapid neutrophil entrapment in the lung vasculature, but in contrast to T‐cell entrapment, this sequestration was ICAM‐1, ICAM‐2, and heparanase independent. Furthermore, neutrophil migration into the bronchoalveolar space induced by LPS inhalation and LPS‐induced leakage of red blood cells into this space were not dependent on lung ICAMs or heparanase activity. Nevertheless, heparanase was critical for neutrophil accumulation in smoke‐exposed lungs. Our results indicate that, whereas T cells use ICAM‐1 and ‐2 for temporary pulmonary entrapment, neutrophils get sequestered and extravasate into inflamed lungs independent of ICAMs. This is the first demonstration that the pulmonary vasculature is differentially recognized by T cells and neutrophils.—Petrovich, E., Feigelson, S. W., Stoler‐Barak, L., Hatzav, M., Solomon, A., Bar‐Shai, A., Ilan, N., Li, J.‐P., Engelhardt, B., Vlodavsky, I., Alon, R. Lung ICAM‐1 and ICAM‐2 support spontaneous intravascular effector lymphocyte entrapment but are not required for neutrophil entrapment or emigration inside endotoxin‐inflamed lungs. FASEB J. 30, 1767–1778 (2016). www.fasebj.org